HKS Misinfo Review 2022
DOI: 10.37016/mr-2020-91
|View full text |Cite
|
Sign up to set email alerts
|

Research note: Tiplines to uncover misinformation on encrypted platforms: A case study of the 2019 Indian general election on WhatsApp

Abstract: There is currently no easy way to discover potentially problematic content on WhatsApp and other end-to-end encrypted platforms at scale. In this paper, we analyze the usefulness of a crowd-sourced tipline through which users can submit content (“tips”) that they want fact-checked. We compared the tips sent to a WhatsApp tipline run during the 2019 Indian general election with the messages circulating in large, public groups on WhatsApp and other social media platforms during the same period. We found that tip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 29 publications
(42 reference statements)
0
15
0
Order By: Relevance
“…New developments in crowdsourcing misinformation may mean citizens can help to stem the tide of misinformation in the future (Kazemi et al, 2021). For example, the enthusiastic responses from users to the WhatsApp tipline in 2019, with tens of thousands of requests by users to have messages fact-checked clearly reflects that not everyone believes the information they see on WhatsApp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…New developments in crowdsourcing misinformation may mean citizens can help to stem the tide of misinformation in the future (Kazemi et al, 2021). For example, the enthusiastic responses from users to the WhatsApp tipline in 2019, with tens of thousands of requests by users to have messages fact-checked clearly reflects that not everyone believes the information they see on WhatsApp.…”
Section: Discussionmentioning
confidence: 99%
“…The project was organized by PROTO-a media research and training organization-and users could submit WhatsApp messages to be fact-checked during the 2019 campaign. Kazemi et al (2021) compare data from WhatsApp users using this tipline with messages circulating in the large public groups mentioned above by Garimella & Eckles (2020), during the 2019 election campaign, and concluded "tiplines can be an effective source for discovering content to fact-check" (Kazemi et al, 2021, p. 1). The study found a total of 1,945 unique messages related to the election, of which the largest cluster included 213 unique messages with misinformation telling voters to ask for a "challenge vote" or "tender vote" if they were not on the voter list or marked as already voting, which was circulated in many languages and reported by the fact-checking team at The Times of India (Kazemi et al, 2021, p. 7).…”
Section: Whatsapp and Facebookmentioning
confidence: 99%
See 1 more Smart Citation
“…Fact‐checking can reduce gullibility towards misinformation (Porter & Wood, 2021), and meta‐analyses reveal that corrections are partly, albeit significantly, effective in reducing people's misperceptions (Chan et al, 2017; Walter & Tukachinsky, 2020), despite the fact that corrections on political misinformation appear to have a weaker effect than correction on, for example, health issues (Walter & Murphy, 2018); they are clearly better than nothing. Given that the closer in time the misinformation and its correction are processed, the better the correction works (Walter & Tukachinsky, 2020), advances in “claim matching” to automatically match repeated instances of misinformation with already published fact‐checks (Kazemi, Garimella, Gaffney, et al, 2021; Shaar et al, 2020) are noteworthy, especially in the context of misinformation tip lines (Kazemi, Garimella, Shahi, et al, 2021). Warning tags against misinformation also appear to be a better‐than‐nothing solution (Walter et al, 2020).…”
Section: State Of the Artmentioning
confidence: 99%
“…The five editions of the lab have been held in 2018-2022, targeting various natural language processing and information retrieval tasks related to factuality [11,12,24,25,61,62,65,66]. The aim is to develop systems that can be useful as supportive technology for investigative journalism, as they could provide help and guidance, thus saving time [30,35,37,42,63,76,97]. For example, a system could automatically identify check-worthy claims, make sure they have not been fact-checked already by a reputable fact-checking organization, and then present them to a journalist for further analysis in a ranked list [83].…”
Section: Introductionmentioning
confidence: 99%